2020
DOI: 10.2139/ssrn.3575633
|View full text |Cite
|
Sign up to set email alerts
|

Economic Preferences and Compliance in the Social Stress Test of the Corona Crisis

Abstract: We test in a survey the impact of economic preferences on compliance and perception during the Corona pandemic. Results show that economic preferences crucially impact citizens' compliance to policies fighting the crisis. Risk tolerance negatively a↵ects citizens' avoidance of crowds, whereas patience helps to do so and to stay home. Present-biased subjects engage in panic buying. Risk tolerance is negatively related with the Corona threat and trust positively resonates with positive media perception. Exploiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This literature shows that individual-level risk aversion, patience, and personality traits are all closely linked to health behaviors ( Galizzi and Wiesen, 2018 ). 4 In the context of the COVID-19 pandemic, several contemporaneous papers examine the relation between health behaviors and self-reported risk and time preferences, trust, and personality ( Zettler et al, 2020 , Müller and Rau, 2020 , Briscese et al, 2020 , Thunström et al, forthcoming ). We add to the literature by showing that, beyond these factors, prosociality is an important and independent determinant of behaviors that are valuable for supporting public health.…”
Section: Introductionmentioning
confidence: 99%
“…This literature shows that individual-level risk aversion, patience, and personality traits are all closely linked to health behaviors ( Galizzi and Wiesen, 2018 ). 4 In the context of the COVID-19 pandemic, several contemporaneous papers examine the relation between health behaviors and self-reported risk and time preferences, trust, and personality ( Zettler et al, 2020 , Müller and Rau, 2020 , Briscese et al, 2020 , Thunström et al, forthcoming ). We add to the literature by showing that, beyond these factors, prosociality is an important and independent determinant of behaviors that are valuable for supporting public health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors reported rumors, safety-seeking behavior, uncertainty, anxiety reduction, and taking control, but also social learning and lacking trust in governmental actions to face the pandemic as reasons for panic buying [see also ( 11 )]. Müller and Rau ( 12 ) recently reported a link between present-bias and panic buying, while patience was associated to staying at home and avoiding crowds. On the other hand, the same study showed that all safety behaviors appear to be linked to fear, or at least COVID-19-related concern.…”
Section: Introductionmentioning
confidence: 99%
“…See Galizzi and Wiesen (2018) for a recent review of the literature linking experimentally and incentive compatible measures of preferences to health behaviors and Cawley and Ruhm (2011) for a review of the theoretical economic literature modelling risky health behaviors. In the context of the COVID-19 pandemic, several contemporaneous papers examine the relation between health behaviors and self-reported risk and time preferences, trust, and personality (Zettler et al, 2020;Müller and Rau, 2020;Briscese et al, 2020;Thunström et al, 2020).…”
Section: Introductionmentioning
confidence: 99%